Tantangan dan Solusi dalam Implementasi Komunikasi Organisasi Prespektif Guru dan Siswa Studi Kasus di MTsN 3 Labuhan Batu - Nasution, Toni; Mesiono, Mesiono; Fattah, Farihin Abdillah; Hirwansyah, Hirwansyah; Al-Faris, Rizza Fikri (VISA: Journal of Vision and Ideas, 2025)
This study aims to identify the challenges and solutions in the implementation of organizational communication at MTsN 3 Labuhan Batu from the perspectives of teachers and students. Effective organizational communication is a crucial element in creating a productive learning environment; however, various obstacles often arise in practice. The study employs a qualitative descriptive approach, utilizing interviews, observations, and documentation for data collection. The findings reveal that teachers face challenges such as time constraints, technological skills, and communication with parents, while students encounter issues related to self-confidence, access to technology, and differences in communication styles. Proposed solutions include interpersonal communication training, improvement of technological facilities, fostering an open communication culture, and enhancing collaboration among teachers, students, and parents. By implementing these solutions, MTsN 3 Labuhan Batu is expected to improve the effectiveness of organizational communication, support the quality of education, and prepare students to face future challenges.